Analisis Performa Persentase Stripping dan Efisiensi Panas Stripper (DA-101) pada Unit Sintesa Urea PUSRI-II B - Enggal Nurisman; Merlinda Ariesty Putri; Mayang Bidari (Journal of Chemical Process Engineering, 2022)
The Synthesis Section in the PUSRI II-B Urea Plant is the main section in the process of making urea fertilizer which will determine the components and quality of urea. The Synthesis Section has three main tools, namely reactor (DC-101), stripper (DA-101), and carbamate condenser (EA-101). The stripper (DA-101) plays a role in the process of separating excess ammonia from urea and decomposing unconverted carbamates from the urea synthesis solution. The separation process in the stripper is called stripping. Carbamate decomposition in the stripper can cause side reactions with the result of excess biuret due to unsuitable operating conditions. This caused in the need to control the operating conditions of the stripper so that the formation of biuret can be minimized. In this study, a stripper performance analysis (DA-101) was carried out from the comparison of design data and actual data in terms of the percentage of NH3 stripping, heat efficiency, and biuret content. The actual data in this study were taken in 5 weeks for 1 month at the end of 2021. From the results of the study, the percentage of NH3 stripping was 76.7329%, 77.1498%, 76.9525%, 76.2190% and 76.10231%. Meanwhile, the heat efficiency is 97.9500%, 93.69%, 95.1200%, 97.1500% and 97.3400%. And the levels of biuret formed are 0.0349 %wt, 0.0671 %wt, 0.0474 %wt, 0.0664 %wt, and 0.0469 %wt. The results of the stripper performance analysis (DA-101) show that the equipment unit is still functioning properly.